2017
DOI: 10.1038/s41598-017-11882-x
|View full text |Cite
|
Sign up to set email alerts
|

A Class II small heat shock protein OsHsp18.0 plays positive roles in both biotic and abiotic defense responses in rice

Abstract: Bacterial blight caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most devastating diseases of rice. However, the molecular mechanism underpinning the Xoo resistance of rice is still not fully understood. Here, we report that a class II small heat shock protein gene, OsHsp18.0, whose expression was differentially induced between a resistant and a susceptible variety in response to Xoo infection, plays positive roles in both biotic and abiotic resistance. The molecular chaperone activity of OsHsp18.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 49 publications
(83 reference statements)
0
19
0
1
Order By: Relevance
“…Therefore, we concluded that TaHSP23.9 plays a positive role in the HSR and acts as a chaperone to repair damage caused by heat stress. In addition, many studies have confirmed that sHSPs can be induced not only by heat stress but also by various stress environments, and OE of sHSPs in transgenic plants can enhance plant tolerance to multiple stresses (Zou et al, 2012;Mu et al, 2013;Zhang et al, 2014Zhang et al, , 2018Kuang et al, 2017). Therefore, we verified the phenotype of TaHSP23.9-OE lines and the expression FIGURE 5 | The relative expression level of TaHSP23.9 under salt stress, and the MDA, total soluble protein, and proline contents and root elongation of Col-0 (WT) and TaHSP23.9 over-expression transgenic lines under heat and salt tress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we concluded that TaHSP23.9 plays a positive role in the HSR and acts as a chaperone to repair damage caused by heat stress. In addition, many studies have confirmed that sHSPs can be induced not only by heat stress but also by various stress environments, and OE of sHSPs in transgenic plants can enhance plant tolerance to multiple stresses (Zou et al, 2012;Mu et al, 2013;Zhang et al, 2014Zhang et al, , 2018Kuang et al, 2017). Therefore, we verified the phenotype of TaHSP23.9-OE lines and the expression FIGURE 5 | The relative expression level of TaHSP23.9 under salt stress, and the MDA, total soluble protein, and proline contents and root elongation of Col-0 (WT) and TaHSP23.9 over-expression transgenic lines under heat and salt tress.…”
Section: Discussionmentioning
confidence: 99%
“…The over-expression (OE) of sHSPs in plants with transgenic technology can not only enhance the heat tolerance of transgenic plants but also improve the abilities of transgenic plants to tolerate other stresses, such as salinity, drought, heavy metals and disease. Most importantly, the OE of sHSPs in transgenic plants does not cause any adverse or defective phenotypes (Kong et al, 2014;Zhang et al, 2014;Fragkostefanakis et al, 2015;Hu et al, 2015;Khaskheli et al, 2015;Sun et al, 2016;Kuang et al, 2017). For example, the OE of a sHSP gene (MasHSP24.4) from wild banana into tomato significantly enhanced tomato tolerance to high temperatures and drought (Mahesh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat TaHsfA2d has been proved to improve tolerance to high temperatures, salinity, and drought stresses in transgenic Arabidopsis plants (Chauhan et al, 2013). Working as molecular chaperones, HSPs belong to multigene families and participate in various biological processes: protein folding, refolding, co-degradation of denatured proteins, and normal growth development (Kuang et al, 2017;Queitsch et al, 2000). The recognized ''refolding machines'', Hsp70 and ERDJ3A, can refold denatured proteins under HS and alleviate stress damage (Ma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As molecular chaperones, Hsps belong to multigene families participate in various biological process of protein 304 folding, refolding, co-degradation of the denature protein and normal growth development (Kuang et al, 2017; 305 Queitsch et al, 2000). The known "refolding machines", consisting of Hsp70 and ERDJ3A, work on the refolding of 306 denatured protein upon heat stress and alleviating the stress damage (Ma et al, 2015).…”
mentioning
confidence: 99%